2018
DOI: 10.1038/s41598-018-32730-6
|View full text |Cite
|
Sign up to set email alerts
|

A study of the correlation between obesity and intestinal flora in school-age children

Abstract: With the improvement of living standards and dietary changes, childhood obesity has increased worldwide. This study aimed to understand the differences of intestinal flora structure between obese and normal children at school-age. Using the next generation sequencing platform, Illumina Miseq, 16S rDNA high-throughput sequencing technology, we analyzed the diversity and relative abundance of intestinal flora in 39 obese and 38 normal control school-age children. First, we categorized gut bacteria on the basis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 24 publications
4
40
0
Order By: Relevance
“…The results α diversity analysis showed no significant difference between the control group and the antibiotic exposure group; however, the β diversity analysis showed significant differences in the structure of two groups of bacteria, which was consistent with the results [7].…”
Section: The Colonization Of Different Gut Microbiota Participate In Weight Changes Of Offspringsupporting
confidence: 88%
“…The results α diversity analysis showed no significant difference between the control group and the antibiotic exposure group; however, the β diversity analysis showed significant differences in the structure of two groups of bacteria, which was consistent with the results [7].…”
Section: The Colonization Of Different Gut Microbiota Participate In Weight Changes Of Offspringsupporting
confidence: 88%
“…It has been suggested that this difference may be caused by female ovarian hormones. Gender differences in intestinal microbiome in addition to microbiome difference between children with overweight/ obesity and children with healthy weight [35] may serve as an alternative explanation.…”
Section: Discussionmentioning
confidence: 99%
“…25 In addition, the abundance and diversity of intestinal flora are reportedly negatively correlated with obesity. 26 Our results showed that the abundance of Bacteroides decreased; furthermore, obesity reduced the diversity of intestinal flora. The overall balance of the intestinal microflora is important in maintenance of homeostasis; 27 intestinal microflora are reportedly disordered in patients with obesity.…”
Section: Discussionmentioning
confidence: 50%